Viewpoint How to Increase the Security of Smart Buildings? - Wendzel, Steffen (Communications of the ACM, 2016)
The author shares insight on ways to increase the security of smart buildings. He discusses the trend on building automation due to market demand. He highlights unsolved problems for smart building security including Internet-based communications, impact of cyber attacks, long-term software development, user-oriented software design, insecure network stacks, and access to standards.